(untitled) (Research, Society and Development, 2020)
The teaching-learning process in higher education institutions comprises the transmission of scientific knowledge from specific disciplines, without being restricted to them, providing a connection between different areas of knowledge, through teaching, extension and research activities, for the promoting expanded training that is in line with the demands of the labor market. In this sense, the execution of the present extension project of the Federal Goiano Institute - Campus Iporá, in Goiás, with an interdisciplinary axis and participation of students from higher education courses in Agribusiness Technology and Technology in Analysis and Development of Systems and professionals in the fields of Agrarian Sciences , Applied Social Sciences and Information Technology, aimed from the survey of specific requirements, to develop a free application for Android mobile devices, in Java language, which helps in the management of information on zootechnical aspects of alternative poultry activity. Thus, it is intended to contribute to the storage and analysis of data registered by the user according to the batch and its specificities (initial and final ration, initial and final weighing, mortality, etc.), among other viability and uniformity indicators that contribute to the statement. decision making in the exercise of the activity in small properties.